Analisis faktor-faktor yang mempengaruhi pembiayaan murabahah dan pengaruhnya terhadap return on asset (ROA) - Romadhona, Firmansyah; Lestari, Sri; Sulistyandari, Sulistyandari (Performance, 2017)
Purpose: The purpose of this research is to analyze the influence of non performing financing, wadiah savings, financing to deposit ratio, and operating income expense toward murabahah financing and the influence to return on asset. Methodology: This research used panel data regression analysis as model to test the hypothesis. The population in this research was Sharia Rural Banking (BPRS) on Indonesia during 2012-2015 consisting of 168 banks. While, the sample of this research was taken by purposive sampling method which was 25 banks. Findings: The result of this research shows that: (1) non performing financing has no effect toward murabahah financing; (2) wadiah savings has positive effect toward murabahah financing; 3) financing to deposit ratio has no effect toward murabahah financing; (4) operating income expense has negative effect toward murabahah financing; and (5) murabahah financing has positive effect toward return on asset. Implications: Implication based on result of this research is the management needs to increase wadiah savings and decrease operating income expense because it can increase the murabahah financing. The management also needs to increase murabahah financing, because in this research it is proven that it can increase the return on asset. Keywords: non performing financing, wadiah savings, financing to deposit ratio, operating income expense, murabahah financing, return on asset.